Largest ideals in Leavitt path algebras. - Cam, Vural; Gil-Canto, Cristóbal; Kanuni, Müge; Siles-Molina, Mercedes (Springer Nature, 2020)
We identify largest ideals in Leavitt path algebras: the largest locally left/right artinian (which is the largest semisimple one), the largest locally left/right noetherian without minimal idempotents, the largest exchange, and the largest purely in nite. This last ideal is described as a direct sum of purely in nite simple pieces plus purely in nite non-simple and non-decomposable pieces. The invariance under ring isomorphisms of these ideals is also studied.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14326?template=romeo
Keywords: Álgebra; Ideales (Algebra); Leavitt path algebra; Socle; Extreme cycle; Line point; Purely infinite ideal